Prevalence of Extra-Cardiac Malformations with Congenital Heart Disease among Hospital Admitted Children- A Study in a Tertiary Level Hospital of Bangladesh - Sarker, Md Ferdousur Rahman; Sadique, Zahir; Begum, Nurun Nahar Fatema; Ahmad, Mushtaq (Journal of Armed Forces Medical College, Bangladesh, 2015)
Introduction: Congenital anomalies are a major cause of stillbirths and infant mortality. In this post genomic era, congenital heart diseases (CHDs) are still the most common and lethal of all birth defects in children. Although most of the CHD occur as a sporadic event many of them have a well-defined genetic basis. This genetic basis is expressed in the form of concomitant occurrence of extra-cardiac malformations (ECM) which may occur alone or as a part of a syndrome. Objective: The present study was designed to find out the burden of CHDs in the hospital admitted children and to find out the prevalence of occurrence of clinically recognizable ECM associated with CHDs. Methods: This is a cross-sectional hospital based study. Total patients admitted during the study period were 5264. Of these 335 patients were found suffering from different types of congenital heart diseases. This gives the hospital admission rate for CHD, as 63.6 per 1000 admission (6.36%). Out of total 335 cases of CHD, 273 (81.5%) were acyanotic and 62 (18.5%) were cyanotic. Among the CHD patients 68 (20.3%) had a significant ECM. Out of the 68 patients with a significant ECM 53 (77.9%) had a clinically recognizable genetic syndrome, whereas 15 cases (22.1%) had a major ECM which was not a part of a syndrome. Conclusion: A high rate of hospital admission is found for CHDs in the pediatric setting, signifying the need for improvement of pediatric cardiology infrastructure in Bangladesh, which should help in providing better medical and surgical care for the patients with CHD. A significant proportion of patients with CHD have associated ECM, implicating a genetic background for the etiology of CHD. It also emphasizes the need for thorough evaluation of patient with CHD for ECM. Journal of Armed Forces Medical College Bangladesh Vol.10(2) 2014